2011
DOI: 10.1371/journal.pone.0023035
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Microbiota in Healthy Adults: Temporal Analysis Reveals Individual and Common Core and Relation to Intestinal Symptoms

Abstract: BackgroundWhile our knowledge of the intestinal microbiota during disease is accumulating, basic information of the microbiota in healthy subjects is still scarce. The aim of this study was to characterize the intestinal microbiota of healthy adults and specifically address its temporal stability, core microbiota and relation with intestinal symptoms. We carried out a longitudinal study by following a set of 15 healthy Finnish subjects for seven weeks and regularly assessed their intestinal bacteria and archae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
247
4
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(276 citation statements)
references
References 69 publications
(127 reference statements)
15
247
4
1
Order By: Relevance
“…However, cluster 5 also contained healthy subgingival samples, indicating that further investigations are necessary to understand and to develop prediction markers for chronic periodontitis. A core community (genera present in at least 50% of the samples) is usually identified in publications and provides a basis for disease diagnosis, prevention, and therapeutic targets (18,19). However, the variability of genera expands as the sample size increases, thus limiting its use for establishing an easy microbiological marker for dysbiosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, cluster 5 also contained healthy subgingival samples, indicating that further investigations are necessary to understand and to develop prediction markers for chronic periodontitis. A core community (genera present in at least 50% of the samples) is usually identified in publications and provides a basis for disease diagnosis, prevention, and therapeutic targets (18,19). However, the variability of genera expands as the sample size increases, thus limiting its use for establishing an easy microbiological marker for dysbiosis.…”
Section: Discussionmentioning
confidence: 99%
“…literature, no consensus on a general human GI microbial core has emerged (Hamady and Knight, 2009;Tap et al, 2009;Turnbaugh et al, 2009;Qin et al, 2010;Claesson et al, 2011;Jalanka-Tuovinen et al, 2011;Salonen et al, 2012). In our cohort we could define a general core microbiota of 96 phylotype-like groups prevalent in all subjects that accounts for 34.7% of the total microbiota (s.d.…”
Section: Uncultured Clostridiales I Uncultured Clostridiales Iimentioning
confidence: 99%
“…Previous studies have shown that GI microbiota is host-specific and GI tract region-specific (Zoetendal et al, 2004;Rajilic-Stojanovic et al, 2009;Jalanka-Tuovinen et al, 2011), aberrant in composition and stability in patients suffering from GI disorders such as Crohn's disease (Seksik et al, 2003), and associated to host energy homeostasis (Backhed et al, 2004;Ley et al, 2006;Turnbaugh et al, 2006;Backhed et al, 2007;Samuel et al, 2008). Analysis of global fecal microbiomes introduced the concept that human GI microbiota appeared to have three distinct structural biometypes called enterotypes (Arumugam et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the gut microbiota of healthy adults is individual specific and relatively stable in time (Claesson et al, 2011;Jalanka-Tuovinen et al, 2011;Rajilić-Stojanović et al, 2013). Two main phyla, Firmicutes and Bacteroidetes, constitute over 90% of the microbiota in healthy adults, followed by Actinobacteria, Proteobacteria and Verrucomicrobia (Claesson et al, 2011;Jalanka-Tuovinen et al, 2011;RingelKulka et al, 2013;Voreades et al, 2014).…”
Section: Introductionmentioning
confidence: 99%